The Effects of Giving Coconut Milk on Aortic Wall Thickness of Rats (Rattus norvegicus strain Wistar) Fed with High Fat Diet (HFD) - Firdaus, Jauhar; Prasetyo, Aris; Wahyudi, Septa Surya; Haniefah, Yumna Rifda (Majalah Obat Tradisional, 2023)
Atherosclerosis is a chronic disease due to fat accumulation in the blood vessel walls. Atherosclerosis is the leading cause of cardiovascular disease. Indonesian people’s habit of consuming coconut milk is suspected of causing dyslipidemia, a risk factor for atherosclerosis, by increasing low-density lipoprotein (LDL). However, other studies suggest that coconut milk can increase high-density lipoprotein (HDL), an antioxidant that prevents atherosclerosis. Because of the different findings, this study aims to determine the effects of coconut milk administration on the aortic wall thickness of rats (Rattus norvegicus strain Wistar) fed a high-fat diet (HFD). This true experimental study used samples of 28 male Wistar rats divided into seven groups. These groups consisted of the normal group (N), the negative control group (Kn), and five treatment groups that received coconut milk at various doses, including 2, 5, 3.75, 5, 7. 5, and 10 ml/kgBW/day. The results obtained were then analyzed using SPSS. The statistical tests used are the independent t-test, one-way ANOVA, LSD post hoc, Pearson correlation test, and regression test. Based on this study, the results showed that giving HFD for 45 days could cause the aortic wall to thicken. Meanwhile, giving an HFD accompanied by coconut milk for 45 days can prevent the thickening of the aortic wall, with the maximum effective dose that can be given being 9.75 ml/kg BW/day.